The power of parables: essays on the comparative study of Jewish and Christian parables - Ottenheijm, Eric; Poorthuis, Marcel; Merz, Annette (Jewish and Christian perspectives series, 2024)
"The Power of Parables documents the surprising ways in which Jewish and Christian parables bridge religion with daily life. This 2019 conference volume rediscovers the original power of parables to shock and affect their audience, which has since been reduced by centuries of preaching and repetition. Not only do parables enhance the perspective on Scripture or the kingdom of heaven, they also change the sensory regime of the audience in perceiving the outer world. The theological differences in their applications appear secondary in view of their powerful rhetoric and suggest a shared genre"--
Keywords: Bible -- Parables -- Congresses; Bible - Paraboles - Congrès; Bible; Konferenzschrift -- 2019 -- Utrecht; Aufsatzsammlung; Parabel; Gleichnis; Bibel; Rabbinische Literatur; Thora